Polymer-based composite solid electrolyte, and preparation method and application thereof
Patent Information
- Application Number
- CN202611174685.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的在于:提供一种聚合物基复合固态电解质及其制备方法和应用,用于解决聚合物固态电解质结晶度较高、晶粒生长难以受控、锂离子传输能力不足、锂金属界面 SEI 生长不均以及界面机械稳定性不足的问题,以实现体相结晶度调控与界面SEI组成调控的双重功能协同,从而提高锂离子传输能力并抑制锂枝晶生长
1)本发明提供的碳化物晶粒抑制剂颗粒可以抑制聚合物体相结晶和晶粒长大,增加非晶区比例,促进聚合物链段运动和锂盐解离,从而提高复合固态电解质的锂离子传输能力。其中,碳化铬等碳化物晶粒抑制剂颗粒具有较高模量和硬度,可增强聚合物电解质锂侧界面的抗形变能力,降低局部凹陷、界面热点和枝晶穿刺风险。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid-state battery technology, and particularly relates to a polymer-based composite solid electrolyte, its preparation method, and its application. Background Technology
[0002] Solid-state batteries are considered a key development direction for next-generation energy storage devices due to their high safety and potential for adaptation to high-energy-density electrode systems. Polymer solid electrolytes offer advantages such as good flexibility, simple film formation processes, and good interfacial contact, making them suitable for lithium metal batteries, quasi-solid-state batteries, and flexible batteries. However, typical polymer electrolytes, especially polymer systems that conduct lithium ions through chain segment movement such as polyethylene oxide, tend to form high crystallinity at room temperature or medium-low temperatures. This leads to insufficient amorphous regions, restricted chain segment movement, and reduced lithium-ion migration. Simultaneously, when polymer electrolytes come into contact with lithium metal anodes, inhomogeneous side reactions often occur at the interface, generating solid electrolyte interfacial films with uneven composition and thickness. This, in turn, causes localized current concentration, dendrite penetration, and cycle degradation.
[0003] In existing technologies, the crystallinity of polymers and the ionic conductivity of composite electrolytes are often reduced by adding inorganic ceramic fillers, oxide nanoparticles, garnet-type solid electrolytes, silicate fibers, or other nanofillers. For example, Chinese patent CN109546211A discloses a composite polymer solid electrolyte membrane, which involves the ionic conductivity testing and membrane structure design of the composite polymer electrolyte membrane. Its focus is on the composite membrane composition and ionic conductivity improvement, but it does not address the structural design for the uniform nucleation of inorganic SEI components such as LiF and Li2O induced by carbide grain inhibitor particles at the lithium-side interface.
[0004] Therefore, the existing technology lacks a systematic understanding of the grain suppression function of carbide particles and has not yet realized that carbide particles can be used as dual-function fillers. Summary of the Invention
[0005] The purpose of this invention is to provide a polymer-based composite solid electrolyte, its preparation method, and its application, which addresses the problems of high crystallinity, uncontrollable grain growth, insufficient lithium-ion transport capacity, uneven growth of the lithium metal interface SEI, and insufficient interfacial mechanical stability in polymer solid electrolytes. This invention achieves a dual-function synergy of bulk crystallinity regulation and interface SEI composition regulation, thereby improving lithium-ion transport capacity and suppressing lithium dendrite growth.
[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a polymer-based composite solid electrolyte, comprising: A polymer electrolyte matrix in which a lithium salt is dispersed; Carbide grain inhibitor particles are distributed in the bulk phase of the polymer electrolyte matrix and / or in the interface region near the negative electrode side; The carbide grain inhibitor particles are used to reduce the crystallinity of the polymer electrolyte matrix and inhibit polymer grain growth, and to induce uniform nucleation of inorganic solid electrolyte interface components containing LiF and / or Li2O in the interface region near the negative electrode.
[0007] Preferably, the carbide grain inhibitor particles are selected from at least one of metal carbides, metalloid carbides, composite carbides, and surface-modified carbides.
[0008] Preferably, the carbide grain inhibitor particles are transition metal carbides, which are selected from at least one of chromium carbide, vanadium carbide, molybdenum carbide, tungsten carbide, titanium carbide, niobium carbide, zirconium carbide, tantalum carbide, and hafnium carbide.
[0009] Preferably, the carbide grain inhibitor particles are chromium carbide, and the chromium carbide is selected from Cr3C2, Cr7C3, Cr... 23 At least one of C6.
[0010] Preferably, the carbide grain inhibitor particles satisfy at least one of the following characteristics: 1) The particle size of the carbide grain inhibitor particles is 100 nm to 5 μm; 2) The content of the carbide grain inhibitor particles is 3-20 wt% based on the total mass of the polymer electrolyte matrix. 3) The mass concentration of the carbide grain inhibitor particles is higher on the side closer to the negative electrode than on the side farther from the negative electrode; 4) The surface of the carbide grain inhibitor particles has at least one of the following: an oxide layer, a fluorinated layer, an oxygen-containing functional group, a fluorine-containing functional group, and a lithium salt adsorption layer.
[0011] Preferably, the polymer electrolyte matrix is selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethyl methacrylate, polycarbonate, polysiloxane, polyphosphate, and polyionic liquid.
[0012] Preferably, the lithium salt is selected from at least one of LiTFSI, LiFSI, LiPF6, LiBOB, LiDFOB, LiClO4, and LiBF4.
[0013] Preferably, the polymer-based composite solid electrolyte further includes auxiliary fillers, which are selected from at least one of oxide solid electrolytes, phosphate solid electrolytes, inorganic oxide fillers, and fluorine-containing inorganic fillers.
[0014] Secondly, the present invention provides a method for preparing a polymer-based composite solid electrolyte, comprising the following steps: S1. Disperse the polymer electrolyte matrix, lithium salt and carbide grain inhibitor particles in a solvent to obtain a composite electrolyte slurry; S2. The composite electrolyte slurry is formed into a film and dried to obtain the polymer-based composite solid electrolyte.
[0015] Preferably, step S1 further includes surface treatment of the carbide grain inhibitor particles, wherein the surface treatment is selected from at least one of ball milling, pickling, plasma treatment, fluorination treatment, lithium salt solution impregnation treatment, and silane coupling treatment.
[0016] Preferably, the film-forming method in step S1 is selected from at least one of the following: blade coating, casting, hot pressing, electrospinning, spraying, impregnation, in-situ polymerization, and 3D printing.
[0017] Thirdly, the present invention provides an electrochemical device comprising a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte located between the positive electrode and the negative electrode, or a polymer-based composite solid electrolyte prepared by the above-described preparation method, wherein the side enriched with carbide grain inhibitor particles faces the negative electrode.
[0018] Preferably, the negative electrode is selected from at least one of lithium metal, lithium-containing composite negative electrode, silicon-based negative electrode, graphite negative electrode, and negative electrode-free current collector.
[0019] Fourthly, the present invention provides an electronic device including the electrochemical device described above.
[0020] Compared with the prior art, the present invention has at least the following beneficial effects: 1) The carbide grain inhibitor particles provided by this invention can inhibit polymer bulk phase crystallization and grain growth, increase the proportion of amorphous regions, promote polymer chain segment movement and lithium salt dissociation, thereby improving the lithium-ion transport capacity of the composite solid electrolyte. Among them, chromium carbide and other carbide grain inhibitor particles have high modulus and hardness, which can enhance the deformation resistance of the lithium side interface of the polymer electrolyte and reduce the risk of local depressions, interface hot spots and dendrite puncture.
[0021] 2) The present invention utilizes carbide grain inhibitor particles near the lithium metal anode side to serve as uniform nucleation sites for inorganic SEI components, thereby making the distribution of components such as LiF and Li2O more uniform and reducing local thick SEI and local impedance surges.
[0022] 3) This invention achieves a composite solid electrolyte with high ionic conductivity, stable lithium-side interface and good cycle safety through the synergistic effect of bulk crystal suppression, interface nucleation and mechanical enhancement. Detailed Implementation
[0023] To make the technical problem to be solved, the technical solution, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.
[0024] In this invention, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0025] In this invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0026] It should be understood that in various embodiments of the present invention, the order of the above-mentioned processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0027] According to a first aspect of the present invention, a polymer-based composite solid electrolyte is provided, comprising: A polymer electrolyte matrix in which lithium salts are dispersed; Carbide grain inhibitor particles are distributed in the bulk phase of the polymer electrolyte matrix and / or in the interfacial region near the negative electrode side; Among them, carbide grain inhibitor particles are used to reduce the crystallinity of the polymer electrolyte matrix and inhibit polymer grain growth, and to induce uniform nucleation of inorganic solid electrolyte interface components containing LiF and / or Li2O in the interface region near the negative electrode.
[0028] Among them, carbide grain inhibitor particles can act as crystallization inhibitors and heterogeneous nucleation control sites in the polymer bulk phase. Their high surface energy, lattice defects, surface polar sites, and interfacial interactions with lithium salts or polymer segments can disrupt the regular stacking of polymer segments, inhibit polymer grain growth, reduce polymer crystallinity, increase the proportion of amorphous regions, and thus improve lithium-ion transport capacity.
[0029] In this context, the side closer to the lithium metal anode refers to the side of the composite solid electrolyte facing the lithium metal, lithium alloy, lithium-containing composite anode, or current collector without an anode in the electrochemical device. Carbide grain inhibitor particles can be uniformly distributed within the polymer electrolyte bulk phase, or they can form a higher concentration enrichment region on the side closer to the lithium metal anode. This enrichment region can be continuous with the polymer bulk phase or exist as a coating layer or hot-pressed layer. On the side closer to the lithium metal anode, carbide grain inhibitor particles can provide a high surface energy interface, defect sites, and surface oxidation / fluorination active sites, allowing inorganic SEI components such as LiF and Li₂O to nucleate more uniformly, reducing the formation of localized large grains and thick SEI. Furthermore, carbides such as chromium carbide typically have high modulus and hardness, which can improve the deformation resistance of the polymer electrolyte on the lithium side, reducing the risk of localized depressions, hot spots, and dendrite punctures.
[0030] In some embodiments of the present invention, the carbide grain inhibitor particles are selected from at least one of metal carbides, metalloid carbides, composite carbides, and surface-modified carbides.
[0031] In some embodiments of the present invention, the carbide grain inhibitor particles are transition metal carbides, which are selected from at least one of chromium carbide, vanadium carbide, molybdenum carbide, tungsten carbide, titanium carbide, niobium carbide, zirconium carbide, tantalum carbide, and hafnium carbide.
[0032] In some embodiments of the present invention, the carbide grain inhibitor particles are chromium carbide, and the chromium carbide is selected from Cr3C2, Cr7C3, Cr... 23 At least one of C6.
[0033] Among them, carbide grain inhibitor particles refer to carbide particulate materials that can inhibit polymer grain growth, reduce polymer crystallinity, or regulate polymer crystal morphology through interfacial interactions, and are selected from Cr3C2, Cr7C3, and Cr 23 At least one of C6, VC, Mo2C, WC, TiC, NbC, ZrC, TaC, HfC, SiC, and B4C; the particles are selected from at least one of nanoparticles, submicron particles, sheet-like particles, short rod-shaped particles, and porous particles; the particle surface may have a naturally occurring oxide layer, or it may be formed by surface treatment to form an oxide layer, a fluorinated layer, an oxygen-containing functional group, a fluorine-containing functional group, or a lithium salt adsorption layer.
[0034] In some embodiments of the present invention, the carbide grain inhibitor particles satisfy at least one of the following characteristics: 1) The particle size of the carbide grain inhibitor particles is 100nm~5μm; 2) The content of carbide grain inhibitor particles is 3-20 wt% based on the total mass of the polymer electrolyte matrix; 3) The mass concentration of carbide grain inhibitor particles is higher on the side closer to the negative electrode than on the side farther from the negative electrode; 4) The surface of the carbide grain inhibitor particles has at least one of the following: an oxide layer, a fluorinated layer, an oxygen-containing functional group, a fluorine-containing functional group, and a lithium salt adsorption layer.
[0035] In some embodiments of the present invention, the polymer electrolyte matrix is selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethyl methacrylate, polycarbonate, polysiloxane, polyphosphate, and polyionic liquid.
[0036] The polymer electrolyte matrix exhibits excellent solubility, film-forming properties, and phase separation control capabilities, making it suitable for processes such as solvent-inducing phase separation and thermally induced phase separation. It can precisely construct pore size and porosity structures with gradient variations along the thickness direction. Polyvinylidene fluoride (PVDF) and its copolymers contain strongly polar CF bonds, demonstrating excellent affinity and swelling capacity for carbonate, ether, and other organic monomers / electrolyte precursor solutions, facilitating the full penetration and uniform distribution of the precursor solution within the gradient channels. When oxide-based solid electrolyte ceramics are used as a blending component, they inherently possess Li... + The improved conductivity allows for the construction of a "dual-continuous" ion transport network within the polymer electrolyte matrix, effectively enhancing overall ionic conductivity. It also improves interfacial compatibility between the substrate and the positive / negative electrodes, reduces space charge layer effects, and improves rate performance and cycle life. By specifically defining the types of polymers and ceramics used, the gradient pore structure substrate achieves synergistic improvements in electrolyte wettability, ion transport, thermal / mechanical stability, interfacial compatibility, and dendrite suppression, which is beneficial for enhancing the energy density and safety of in-situ polymerized solid-state lithium batteries.
[0037] In some embodiments of the present invention, the lithium salt is selected from at least one of LiTFSI, LiFSI, LiPF6, LiBOB, LiDFOB, LiClO4, and LiBF4.
[0038] In some embodiments of the present invention, the polymer-based composite solid electrolyte further includes auxiliary fillers, which are selected from at least one of oxide solid electrolytes, phosphate solid electrolytes, inorganic oxide fillers, and fluorine-containing inorganic fillers.
[0039] According to a second aspect of the present invention, the present invention provides a method for preparing a polymer-based composite solid electrolyte, comprising the following steps: S1. Disperse the polymer electrolyte matrix, lithium salt and carbide grain inhibitor particles in a solvent to obtain a composite electrolyte slurry; S2. The composite electrolyte slurry is formed into a film and dried to obtain a polymer-based composite solid electrolyte.
[0040] The preparation methods of polymer-based composite solid electrolytes also include solution blending for film formation, interface coating, gradient coating, hot pressing, electrospinning, spraying, impregnation, and in-situ polymerization. During these processes, by controlling the particle size, content, surface state, and spatial distribution of carbide grain inhibitor particles, bulk uniformly dispersed, lithium-side enriched, or bulk-interface synergistic composite solid electrolytes can be obtained.
[0041] In some embodiments of the present invention, step S1 further includes surface treatment of the carbide grain inhibitor particles, wherein the surface treatment is selected from at least one of ball milling, pickling, plasma treatment, fluorination treatment, lithium salt solution impregnation treatment, and silane coupling treatment.
[0042] Among these methods, surface treatment of carbide grain inhibitor particles helps to regulate lithium-ion behavior. This, combined with the design of a higher concentration enrichment region of carbides on one side of the lithium metal anode, creates a synergistic effect, effectively solving the problems of dendrite growth, interface instability, and poor contact in the lithium metal anode system. This significantly improves the battery's safety, cycle life, and coulombic efficiency. By selecting functional materials with lithiophilicity, high ion conductivity, interface stability, and good process compatibility, the anode-side modification layer can not only effectively suppress lithium dendrites but also actively optimize lithium deposition morphology, stabilize the SEI, and improve interface ion transport. Furthermore, it deeply synergizes with the gradient pore structure and in-situ polymerization process, thereby significantly improving the energy density, cycle stability, and safety of solid-state lithium batteries.
[0043] In some embodiments of the present invention, the film-forming method in step S1 is selected from at least one of the following: blade coating, casting, hot pressing, electrospinning, spraying, impregnation, in-situ polymerization, and 3D printing.
[0044] According to a third aspect of the present invention, the present invention provides an electrochemical device comprising a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte located between the positive electrode and the negative electrode, or a polymer-based composite solid electrolyte prepared by the above-described preparation method, wherein the side enriched with carbide grain inhibitor particles faces the negative electrode. The electrochemical device is selected from at least one of lithium metal batteries, lithium-ion batteries, quasi-solid-state batteries, all-solid-state batteries, and negative electrode-free lithium metal batteries. The battery preparation method comprises the following steps: (1) placing the polymer-based composite solid electrolyte between the positive electrode and the negative electrode, such that the side enriched with carbides faces the negative electrode, and the side with relatively less enriched carbides faces the positive electrode; (2) by applying a certain pressure to the stacked electrode-electrolyte structure, the resulting battery combines the synergistic effects of solid phase crystal suppression, interface nucleation, and mechanical reinforcement, and can achieve high ionic conductivity, low interface impedance, and excellent lithium dendrite suppression capability while ensuring mechanical support and safety.
[0045] In some embodiments of the present invention, the negative electrode is selected from at least one of lithium metal, lithium-containing composite negative electrode, silicon-based negative electrode, graphite negative electrode, and negative electrode-free current collector.
[0046] According to a fourth aspect of the present invention, an electronic device is provided, comprising the electrochemical device described above.
[0047] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0048] Example 1
[0049] Preparation of polymer-based composite solid electrolytes 1) Weigh out polyethylene oxide and LiTFSI, wherein the ethylene oxide unit and Li + The molar ratio of the two components is 16:1. They are dissolved in acetonitrile and stirred to form a homogeneous polymer salt solution. Chromium carbide particles with an average particle size of 100 nm are weighed and added to the above solution at 10 wt% of the total polymer mass. The solution is ultrasonically dispersed for 30 minutes and then stirred for another 12 hours to obtain a composite electrolyte slurry.
[0050] 2) The above composite electrolyte slurry was coated onto a polytetrafluoroethylene plate. After the solvent evaporated at room temperature, it was vacuum dried at 60°C for 24 hours, and then hot-pressed at 70°C for 5 minutes to obtain a polymer-based composite solid electrolyte.
[0051] Example 2
[0052] Preparation of lithium carbide-enriched polymer-based composite solid electrolyte 1) A polymer-based composite solid electrolyte without chromium carbide particles was prepared according to the method of Example 1.
[0053] 2) Weigh chromium carbide particles with an average particle size of 80 nm, polyvinylidene fluoride-hexafluoropropylene and LiFSI and disperse them in N,N-dimethylformamide to obtain lithium-side interface slurry, wherein chromium carbide particles account for 30 wt% of the total solid mass of lithium-side interface slurry.
[0054] 3) The above lithium-side interface slurry is coated on one side of the polymer-based composite solid electrolyte, dried, and then hot-pressed at 60 °C to form a lithium-side enriched polymer-based composite solid electrolyte with a thickness of 5 μm.
[0055] Example 3
[0056] Preparation of carbide gradient polymer-based composite solid electrolyte 1) Weigh out polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene and LiFSI and dissolve them in a mixed solvent of acetonitrile and N,N-dimethylformamide to obtain a polymer salt solution.
[0057] 2) Chromium carbide and vanadium carbide are mixed at a mass ratio of 1:1, ball-milled, and then added to a polymer salt solution to obtain a first slurry, wherein the carbide composite particles account for 3 wt% of the total solid mass of the first slurry. A second slurry is prepared separately, wherein the carbide composite particles account for 20 wt% of the total solid mass of the second slurry.
[0058] 3) First, the first slurry is cast to form a bulk phase layer, and then the second slurry is coated on one side of the bulk phase layer. After drying and hot pressing, a carbide gradient polymer-based composite solid electrolyte is obtained.
[0059] Example 4
[0060] The difference from Example 1 is that chromium carbide in step (1) is replaced with fluorinated chromium carbide. Specifically, chromium carbide particles are immersed in a fluorinated lithium salt solution and then dried to allow the chromium carbide surface to adsorb fluorinated anions or form a fluorinated surface layer. In step (1), polyethylene oxide is replaced with polyvinylidene fluoride-hexafluoropropylene and polymethyl methacrylate. The remaining steps are the same as in Example 1.
[0061] Comparative Example 1 Unlike Example 1, step (1) does not involve the addition of chromium carbide, while the remaining steps are the same as in Example 1.
[0062] Comparative Example 2 The difference from Example 1 is that chromium carbide in step (1) is replaced with Al2O3, and the rest of the steps are the same as in Example 1.
[0063] Performance testing To verify the effect of the carbide grain inhibitor particles of the present invention on polymer crystallization behavior, ion transport capacity, and lithium-side interface stability, the composite solid electrolytes obtained in the above examples and comparative examples were tested. Unless otherwise specified, the test temperature was 25 °C, the electrolyte film thickness was controlled within the range of 80-120 μm, and all electrolytes were thoroughly dried under vacuum conditions before battery assembly.
[0064] 1) Crystallinity Test: Differential scanning calorimetry (DSC) was used to test the enthalpy of fusion of each electrolyte membrane. During the test, an appropriate amount of the electrolyte membrane to be tested was placed in an aluminum crucible, and the temperature was increased at a preset rate under a nitrogen atmosphere. The melting peak and enthalpy of the polymer phase were recorded. The relative crystallinity of the sample was calculated based on the theoretical enthalpy of fusion of pure polyethylene oxide, which was used to evaluate the inhibitory effect of carbide grain growth inhibitor particles on the orderly packing of polymer chains and grain growth.
[0065] 2) Ionic conductivity test: The electrolyte membranes obtained in the examples and comparative examples were cut into circular pieces and sandwiched between two stainless steel blocking electrodes to assemble a stainless steel sheet|electrolyte|stainless steel sheet test cell. AC impedance testing was performed using an electrochemical workstation with a frequency range of 10 Hz. 6 -10 -2 The perturbation voltage is 10mV and the frequency is Hz. The bulk impedance R is read from the intersection of the high-frequency region and the real axis of the Nyquist plot. b And calculate the ionic conductivity.
[0066] 3) Lithium-side interface stability and critical current density test: The electrolyte membranes obtained in the examples and comparative examples were sandwiched between two lithium metal sheets to assemble a Li|electrolyte|Li symmetric battery, wherein the side enriched with carbide grain inhibitor particles faces the lithium metal anode; the symmetric battery was left to stand at 25°C for 6-12 hours to stabilize the interface, and then a constant current lithium deposition / stripping test was performed.
[0067] The lithium deposition / stripping stability test conditions were: current density of 0.2 mA·cm⁻¹. -2 The single deposition / stripping capacity is 0.2 mA·cm³. -2 The battery polarization voltage was recorded as a function of cycle time to evaluate the stability of the lithium-side interface.
[0068] The critical current density test conditions are: initial current density of 0.1 mA·cm⁻¹ -2 At each current density, deposition / stripping is performed for a fixed time or capacity, and after several cycles, it is accelerated at 0.1 mA·cm⁻¹. -2 The current density is gradually increased until the battery experiences a sudden voltage drop, short circuit, or abnormal increase in polarization voltage. The maximum current density at which the battery can operate stably before a short circuit is denoted as the critical current density.
[0069] 4) Rate Performance and Capacity Retention Test: The polymer-based composite solid electrolytes obtained in the examples and comparative examples were assembled into NCM811||Li full cells for rate performance and cycle stability testing. The positive electrode sheet can be obtained by mixing NCM811 active material, conductive agent, and binder in a preset mass ratio to form a slurry, coating it onto an aluminum foil current collector, and then drying, rolling, and cutting it into sheets; the negative electrode is a lithium metal sheet. During battery assembly, the electrolyte membrane is placed between the positive electrode sheet and the lithium metal negative electrode, with the carbide-rich side facing the lithium metal negative electrode.
[0070] The rate performance test conditions are as follows: the voltage range is set to 2.8-4.3 V, and the nominal specific capacity is calculated based on the mass of the positive electrode active material; the battery is first activated at a rate of 0.1 C for 2 cycles, and then constant current charge and discharge tests are performed sequentially at rates of 0.2 C, 0.5 C, 1.0 C, 2.0 C, and 3.0 C, with several cycles at each rate, and the discharge specific capacity at each rate is recorded.
[0071] The capacity retention rate test conditions are as follows: The battery is subjected to a long-cycle test at 25 ℃ and a rate of 1.0 C. The discharge capacity of the first cycle or the stable cycle after activation and the discharge capacity of the Nth cycle are recorded, and the capacity retention rate is calculated according to the following formula: Capacity retention rate (%) = C N / C1×100%; Where C1 is the discharge capacity of the first cycle or the stable cycle after activation, C N This represents the discharge capacity of the Nth cycle. N can be selected as 100, 300, 500, or 1000 cycles depending on the experimental design.
[0072] Table 1. Crystallinity, ionic conductivity and lithium-side interface stability of composite solid electrolytes from different samples
[0073] As shown in Table 1, compared to Comparative Example 1 which did not contain carbide grain growth inhibitor particles, the relative crystallinity of Examples 1-4 was significantly reduced, indicating that the carbide particles can effectively disrupt the orderly stacking of polymer segments and inhibit polymer grain growth. In particular, Examples 3 and 4, due to their combined effects of solid phase inhibition and lithium-side interface regulation, achieved ionic conductivity increases to 6.8 × 10⁻⁶. -4 S·cm -1 and 7.3×10 -4 S·cm -1 All of them were higher than those of Comparative Example 1 and Comparative Example 2.
[0074] Furthermore, in Examples 2-4, after the carbide grain inhibitor particles were enriched near the lithium metal anode or treated with surface fluorination, the stable cycle time of the Li|electrolyte|Li symmetric battery was significantly extended and the critical current density was increased. This indicates that the carbide particles not only play a role in inhibiting bulk crystallization, but also enhance the mechanical stability of the lithium-side interface and reduce the risk of dendrite puncture.
[0075] Table 2. Specific capacity and rate performance of different NCM811||Li batteries. (Based on the mass calculation of the positive electrode active material)
[0076] Table 2 shows that Examples 1-4 all exhibited higher discharge specific capacities than Comparative Examples 1 and 2 at rates from 0.2C to 3.0C. This indicates that the carbide grain inhibitor particles, by reducing polymer crystallinity, can improve the lithium-ion migration ability in the electrolyte and enhance ion supply under high-rate conditions. Examples 3 and 4 maintained 146 mAh·g at 3.0C. -1 and 151mAh·g -1The discharge specific capacity indicates that the gradient distribution and surface fluorination treatment are beneficial for simultaneously ensuring bulk conductivity and lithium-side interface stability.
[0077] In summary, the carbide grain inhibitor particles of this invention can reduce crystallinity and increase ionic conductivity in the polymer bulk phase, and promote the uniform nucleation of inorganic SEI components such as LiF and Li2O and improve interfacial mechanical stability near the lithium metal anode. Therefore, this invention, through the synergistic effect of bulk crystal inhibition, interfacial nucleation, and mechanical enhancement, is beneficial to improving the rate performance, cycle stability, and anti-dendrying ability of polymer-based composite solid electrolytes.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A polymer-based composite solid electrolyte, characterized in that, include: A polymer electrolyte matrix in which a lithium salt is dispersed; Carbide grain inhibitor particles are distributed in the bulk phase of the polymer electrolyte matrix and / or in the interface region near the negative electrode side; The carbide grain inhibitor particles are used to reduce the crystallinity of the polymer electrolyte matrix and inhibit polymer grain growth, and to induce uniform nucleation of inorganic solid electrolyte interface components containing LiF and / or Li2O in the interface region near the negative electrode.
2. The polymer-based composite solid electrolyte according to claim 1, characterized in that, The carbide grain inhibitor particles are selected from at least one of metal carbides, metalloid carbides, composite carbides, and surface-modified carbides.
3. The polymer-based composite solid electrolyte according to claim 2, characterized in that, The carbide grain inhibitor particles are transition metal carbides, which are selected from at least one of chromium carbide, vanadium carbide, molybdenum carbide, tungsten carbide, titanium carbide, niobium carbide, zirconium carbide, tantalum carbide, and hafnium carbide.
4. The polymer-based composite solid electrolyte according to claim 3, characterized in that, The carbide grain inhibitor particles are chromium carbide, and the chromium carbide is selected from Cr3C2, Cr7C3, and Cr... 23 At least one of C6.
5. The polymer-based composite solid electrolyte according to claim 1, characterized in that, The carbide grain inhibitor particles satisfy at least one of the following characteristics: 1) The particle size of the carbide grain inhibitor particles is 100 nm to 5 μm; 2) The content of the carbide grain inhibitor particles is 3-20 wt% based on the total mass of the polymer electrolyte matrix. 3) The mass concentration of the carbide grain inhibitor particles is higher on the side closer to the negative electrode than on the side farther from the negative electrode; 4) The surface of the carbide grain inhibitor particles has at least one of the following: an oxide layer, a fluorinated layer, an oxygen-containing functional group, a fluorine-containing functional group, and a lithium salt adsorption layer.
6. The polymer-based composite solid electrolyte according to claim 1, characterized in that, The polymer electrolyte matrix is selected from at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethyl methacrylate, polycarbonate, polysiloxane, polyphosphate, and polyionic liquid; And / or, the lithium salt is selected from at least one of LiTFSI, LiFSI, LiPF6, LiBOB, LiDFOB, LiClO4, and LiBF4; And / or, the polymer-based composite solid electrolyte further includes auxiliary fillers, wherein the auxiliary fillers are selected from at least one of oxide solid electrolytes, phosphate solid electrolytes, inorganic oxide fillers, and fluorine-containing inorganic fillers.
7. A method for preparing a polymer-based composite solid electrolyte according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Disperse the polymer electrolyte matrix, lithium salt and carbide grain inhibitor particles in a solvent to obtain a composite electrolyte slurry; S2. The composite electrolyte slurry is formed into a film and dried to obtain the polymer-based composite solid electrolyte.
8. The preparation method according to claim 7, characterized in that, Step S1 further includes surface treatment of the carbide grain inhibitor particles, wherein the surface treatment is selected from at least one of ball milling, pickling, plasma treatment, fluorination treatment, lithium salt solution impregnation treatment, and silane coupling treatment.
9. The preparation method according to claim 7, characterized in that, In step S1, the film formation method is selected from at least one of the following: blade coating, casting, hot pressing, electrospinning, spraying, impregnation, in-situ polymerization, and 3D printing.
10. An electrochemical device, characterized in that, The polymer-based composite solid electrolyte comprises a positive electrode, a negative electrode, and a polymer-based composite solid electrolyte as described in any one of claims 1-6, or is prepared by any one of claims 7-9, wherein the side enriched with carbide grain inhibitor particles faces the negative electrode.
11. The electrochemical device according to claim 10, characterized in that, The negative electrode is selected from at least one of lithium metal, lithium-containing composite negative electrode, silicon-based negative electrode, graphite negative electrode, and negative electrode-free current collector.
12. An electronic device, characterized in that, Includes the electrochemical device as described in claim 10 or 11.
Citation Information
Patent Citations
Composite polymer solid-state electrolyte membrane and preparation method thereof
CN109546211A